Posterior cornea and thickness changes after scleral lens wear in keratoconus patients. Issue 1 (February 2019) - Serramito, Maria; Carpena-Torres, Carlos; Carballo, Jesús; Piñero, David; Lipson, Michael; Carracedo, Gonzalo
Highlights: The posterior corneal curvature after scleral lens wearing has never been studied. A flattening curvature appears in nasal quadrant in intracorneal ring patients and in inferior hemisphere in keratoconus. The cornea is slightly thinner after scleral lens wear except in the apex and temporal quadrant. Abstract: Purpose: To evaluate the changes in the corneal thickness, anterior chamber depth and posterior corneal curvature and aberrations after scleral lens wear in keratoconus patients with and without intrastromal corneal ring segments (ICRS). Methods: Twenty-six keratoconus subjects (36.95 ± 8.95 years) were evaluated after 8 h of scleral lens wear. The subjects were divided into two groups: those with ICRS (ICRS group) and without ICRS (KC group). The study variables evaluated before and immediately after scleral lens wear included corneal thickness evaluated in different quadrants, posterior corneal curvature at 2, 4, 6 and 8 mm of corneal diameter, posterior corneal aberrations for 4, 6 and 8 mm of pupil size and anterior chamber depth. Results: There was a statistically significant corneal thinning (p < 0.05) in the inferior region of the KC group and in the superior region of the ICRS group. No change (p > 0.05) in the anterior chamber depth was found. The KC group showed a steepening (p < 0.05) in the temporal quadrant and a flattening that mainly affected to the superior-nasal quadrant. The ICRS group showed a steepening (p < 0.05) that mainly affected to the superior-nasal quadrant. Regarding posterior corneal aberrations, only changes (p < 0.05) in Z4 for 8 mm and Z8 for 4 mm were found in the KC group. Conclusions: Short-term scleral lens wear showed a thinning of the cornea and changes in the posterior corneal curvature affects different regions in keratoconus patients with and without ICRS.